Fundamental studies of sorghum roughages and grains. I. A study of the value of pelleting sorghum grain. II. A study of the value of levels of hormone and synthetic hormone-like substances. - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Previous work has shown that rate of gain and carcass quality are essentially the same with sorghum grain and corn when self-fed in a beef fattening ration (Kansas Agricultural experiment Station Circulars 308 a20, and 335). However, the animals eat more sorghum grain than corn per pound of gain. Because of its relatively small size, uniform preparation of the sorghum grain is more difficult than for the larger corn grain. This is a preliminary test to evaluate grinding sorghum grain to a meal and then making it into a pellet. Source and level of hormones and synthetic hormone-like substances used as implants are also being studied.
Keywords: Beef; Gain; Sorghum; Hormone